PERAN JAMINAN SOSIAL KETENAGAKERJAAN DALAM KESEJAHTERAAN PEKERJA DI MASA MENDATANG PADA PROGRAM BPJS KETENAGAKERJAAN - khofifah, nurul; Bakhri, Saiful; Wahyudi (Jurnal Ilmiah Ekonomi Bisnis, 2023)
Workers, workers and employers in carrying out their duties certainly each have risks that may occur, both the risk of illness due to their work, the risk of work accidents, the risk of disability, the risk of job loss and even the risk of death. Workers need social security to prevent new poverty when these risks occur. This labor social security is a protection that will provide benefits for the workforce itself and their heirs, and increase welfare in the future if unexpected things happen, one of which is a work accident. Forms of social security for workers include: Old Age Insurance, Work Accident Insurance, Death Insurance, Pension Insurance, Job Loss Insurance. This research uses qualitative methods, namely research procedures by producing descriptive data in the form of words and interview results. The conclusion of this study is the lack of awareness from the workforce or the public about the benefits of BPJS Employment on risks in employment.